Phenomenon of Money: Social and Psychological Essence and Functions - Zubiashvily, Irina; Kocharian, Alexander; VitaliiLunov; Barinova, Natalia; Onufriieva, Liana (International Journal of Psychosocial Rehabilitation, 2020)
In this article social and psychological essence of money is considered as means of person’s entering the world of economy, i.e. as a factor of economic socialization. Psychological research of money gives an opportunity to study a social and psychological aspect of money connected with problems of psychological perception of money by people, society, country; to study connection between money and goals, motives, interests appearing in different forms of economic activity, influence of money on people’s consciousness, their way of life and behavior, relations prevailing in the society. Money has influence on all spheres of life activity from economic to spiritual and political. Money is considered as a special economic and psychological reality, a special symbol. Peculiarity of money consists in uniting material and ideal, thing and thought, and provides for its objective and subjective availability represented in the consciousness.